2003
DOI: 10.1038/sj.ijo.0802272
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning in the obese before and after weight reduction: construct validity and responsiveness of the Obesity-related Problems scale

Abstract: OBJECTIVE:The Obesity-related Problems scale (OP) is a self-assessment module developed to measure the impacts of obesity on psychosocial functioning. Our principal aim was to evaluate the construct validity and responsiveness of the OP scale. Our specific aims were to test: (1) the psychometric performance of OP; (2) if OP scores differed by gender and weight category; (3) if OP scores are inversely related to mental well-being; (4) if weight reduction in the obese is accompanied by improvements in psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
211
2
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(248 citation statements)
references
References 38 publications
22
211
2
13
Order By: Relevance
“…This indicates that short-term reports (up to 1 year) of HRQL effects after bariatric surgery should be interpreted with caution. 7 Previously reported results from the SOS study have shown a positive relationship between weight reduction and HRQL improvements up to 4 years after intervention. 2,5,7 In the present study, we demonstrated that weight reduction after 6 and 10 years was also associated with improvements in HRQL, except for change in anxiety.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This indicates that short-term reports (up to 1 year) of HRQL effects after bariatric surgery should be interpreted with caution. 7 Previously reported results from the SOS study have shown a positive relationship between weight reduction and HRQL improvements up to 4 years after intervention. 2,5,7 In the present study, we demonstrated that weight reduction after 6 and 10 years was also associated with improvements in HRQL, except for change in anxiety.…”
Section: Discussionmentioning
confidence: 91%
“…7 Previously reported results from the SOS study have shown a positive relationship between weight reduction and HRQL improvements up to 4 years after intervention. 2,5,7 In the present study, we demonstrated that weight reduction after 6 and 10 years was also associated with improvements in HRQL, except for change in anxiety. We also concluded that weight regain after previous weight loss was associated with deteriorations in all HRQL domains, except anxiety.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations